PENGARUH PENYULUHAN TENTANG SAYUR DAN BUAH DENGAN METODE CERAMAH DAN BERMAIN TEBAK RASA TERHADAP PENGETAHUAN DAN SIKAP DALAM KONSUMSI SAYUR DAN BUAH PADA SISWA SD NEGERI 067254 KECAMATAN MEDAN DELI TAHUN 2016 - Iana Tresia A Sibagariang; Albiner Siagian; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Vegetables and fruits have many benefits for health because containt vitamins, minerals, and fibers. But consumption of these food is still low for primary school student. It is because the wrong behaviour of children. To increase the consumption of vegetables and fruit, it need health promotion to controlling behavioral interventions such as knowledge and attitudes. The purpose of this research is to know influence of the nutritional extension with discourse and playing game guess the taste of vegetable and fruit methodson knowledge and attitude of primary school students in SD Negeri 067254 Medan. This study was quasi experimental study that used posttest only with control group. The sample of this study was 104 student who was taken from fourth and fifth grade. The extension was done by dividing the respondent into three experimental groups and one control group. The posttest result was analyzed with degree of deviation 5%. The result was showed that knowledge and attitudes for several student in the control group still low, while the groups that given discourse or playing method and both of the methods had good categories. Independent-sample t test showed that there was mean difference significant for control group with the three experimental group. Meanwhile, ANOVA One Way with Bonferroni Analysis to compare the better methods, there was different mean of the three methods, it was: discourse and playing method group. The suggestion from this research is for the readers can givenutritional extension specially about vegetables and fruits by discourseand playing game guess the taste of vegetables and fruis methods for primary school student. Keywords: nutritional extension, discourse method, playing games method, primary school student